Shifts in soil traits and arbuscular mycorrhizal symbiosis represent the conservation status of Araucaria araucana forests and the effects after fire events - Chávez, Daniel; Machuca, Ángela; Fuentes Ramirez, Andrés; Fernández, Natalia Verónica; Cornejo, Pablo (Forest Ecology and Management)
Araucaria araucana is a long-lived native conifer from the sub-Antarctic Andean forests of South America. Currently, the species is classified as endangered due to fragmentation, deforestation and increasing fire events affecting southern Chile. Although fire is a key factor shaping the dynamics of A. araucana forests, the impact of fire on the chemical and microbiological soil properties remains elusive. Here, we aimed to characterize the (bio)chemical and microbiological soil traits in different sites of the Andes and the Coastal range of southern Chile, as a way to describe the conservation status of A. araucana forests in contrasting environments with different fire history. The study was conducted in old-growth A. araucana forests within protected areas affected by different fire events during the last 18 years. Roots were analyzed for arbuscular mycorrhizal (AM) colonization and soil samples were processed for (bio)chemical and microbiological analyses. Our results revealed that AM colonization was strongly affected by fire, being closely related with the acid phosphatase and β-glucosidase enzymatic activities, which also showed lower values in fire-affected sites. Glomalin-related protein in the soil was also a good indicator of soil stability associated to environments non-affected by fire. Based on our results, the conservation status benchmark for A. araucana is in the Coastal range, showing high rates of AM colonization, fungal structures and biochemical activities in environments subjected to minor geological risks and no fire events. This research provides helpful information for finding efficient biological inoculants, including indigenous AM fungal species, which can help to enhance A. araucana plantlets with an optimized rhizosphere oriented to the restoration of burned A. araucana forests in south-central Chile. Fil: Chávez, Daniel. Universidad de la Frontera. Núcleo Científico y Tecnológico En Recursos Naturales (bioren-ufro). Departamento de Ciencias Químicas y Recursos Naturales. ...